ПРАВОВА ПРИРОДА СМАРТКОНТРАКТУ ТА ПРОБЛЕМИ ЙОГО ЗАСТОСУВАННЯ У СФЕРІ ЦИФРОВИХ АКТИВІВ - Nekit, K.H. (Економіка та право, 2023)
The article looks into the concept and legal nature of smart contracts, as well as the issues that arise during the use of smart contracts in the field of digital assets. The technical and legal aspects of the concept of a smart contract are considered. Models of use of smart contracts are described. Scientific and legislative approaches to determining the legal nature of smart contracts are presented. The dual legal nature of a legal smart contract is analyzed: as a form of transaction and an object of copyright. Some issues in the field of protection of the rights of smart contract parties are considered. Based on the findings, temporary solutions in the field of using smart contracts are proposed. REFERENCES1. Alabi F. Taking Contracting Digital: Examination of the Smart Contracts Experiment. SSRN. 10.08.2017. 22 p. http://dx.doi.org/10.2139/ssrn.30158432. Baranov O.A. Internet rechei (IoT): pravovi problemy zastosuvannia rozumnykh kontraktiv. Informatsiia i pravo. 2017. No. 4 (23). P. 26-40 [in Ukrainian].3. Szabo N. The idea of smart contracts. 1997. URL: https://www.fon.hum.uva.nl/rob/Courses/InformationInSpeech/CDROM/Literature/LOTwinterschool2006/szabo.best.vwh.net/idea.html4. Smart contracts and distributed ledger — a legal perspective. ISDA Linklaters Whitepaper. 03.08.2017. 23 p. URL: https://www.isda.org/a/6EKDE/smart-contracts-and-distributed-ledger-a-legal-perspective.pdf5. Grin' O.S., Grin' E.S., Solov'ev A.V. Pravovaja konstrukcija smart-kontrakta: juridicheskaja priroda i sfera primenenija. Lex russica. 2019. No. 8 (153). P. 51-62 [in Russian].6. Bogdanova E.E. Problemy primenenija smart-kontraktov v sdelkah s virtual'nym imushhestvom. Lex russica. 2019. No. 7 (152). P. 108-118 [in Russian].7. Novoselova L. “Tokenizacija” objektov grazhdanskogo prava. Hozjajstvo i pravo. 2017. No. 12. P. 29-44 [in Russian].8. Vashkevich A.A. Smart-kontrakty: chto, zachem i kak. Moscow: Simploer, 2018. 89 p. [in Russian].9. Savel'ev A.I. Dogovornoe pravo 2.0: “umnye kontrakty” kak nachalo konca klassicheskogo dogovornogo prava. Vestnik grazhdanskogo prava. 2016. No. 3. P. 32-60 [in Russian].10. Efimova L.G., Sizemova O.B. Pravovaja priroda smart-kontrakta. Bankovskoe pravo. 2019. No. 1. P. 23-30 [in Russian].11. Somova E.V. Smart-kontrakt v dogovornom prave. Zhurnal zarubezhnogo zakonodatel'stva i sravnitel'nogo pravovedenija. 2019. No. 2. P. 79-86 [in Russian].12. Tjul'kanov A. Smart-kontrakty — dogovory ili tehnicheskie sredstva? URL: https://zakon.ru/blog/2017/4/7/smartkontrakty__dogovory_ili_tehnicheskie_sredstva [in Russian].13. Mitrofanova I.A. Zakonodatel'noe regulirovanie “umnyh” kontraktov: problemy i perspektivy razvitija. Pravovaja paradigma. 2018. No. 4 (17). P. 22-28 [in Russian].14. Kirillova E.A., Bogdan V.V., Lagutin I.B., Gorevoy E.D. Legal status of smart contracts: features, role, significance. Juridicas Cuc. 2019. No. 15 (1). Рp. 285-300. https://doi.org/10.17981/juridcuc.15.1.2019.1115. Tasca P. Digital Currencies: Principles, Trends, Opportunities, and Risks. SSRN. 07.09.2015. 110 p. http://dx.doi.org/10.2139/ssrn.265759816. Mukherjee A. Smart Contracts – Another Feather in UNCITRAL’s Cap’. Cornell International Law Journal. Vol. 6. 08.02.2018. URL: https://cornellilj.org/2018/02/08/smart-contracts-another-feather-in-uncitrals-cap/17. De Caria R. The Legal Meaning of Smart Contracts. European Review of Private Law. European Review of Private Law. 2018. Vol. 26. Iss. 6. P. 731–751. https://doi.org/10.54648/erpl201805218. Lukojanov N.V. Pravovye aspekty zakljuchenija, izmenenija i prekrashhenija smart-kontraktov. Juridicheskie issledovanija. 2018. No. 11. P. 28-35 [in Russian].19. Tjul'kanov A. Blokchejnu — net, smart-kontraktam — da: zakonodateli Nevady opredelilis' s ponjatijami. Zakon.ru. 2017. URL: https://zakon.ru/blog/2017/06/19/blokchejnu_-_da_smart-kontraktam_-_net_zakonodateli_nevady_opredelilis_s_ponyatiyami [in Russian].20. UK Law Commission. Thirteenth Program of Law Reform. 2017. URL: https://s3-eu-west-2.amazonaws.com/lawcomprod-storage-11jsxou24uy7q/uploads/2017/12/13th-Programme-of-Law-Reform.pdf21. Law Commission to review treatment of smart contracts & digital assets. Simmons+Simmons. 29.10.2022. URL: https://www.simmons-simmons.com/en/publications/ckgv30cctoxie0951t4x3h8z9/law-commission-to-reviewtreatment-of-smart-contracts-digital-assets22. Chub D.V. Pravovoe regulirovanie smart-kontraktov vo Francii. Aktual'nye problemy rossijskogo prava. 2019. No. 8 (105). P. 151-157 [in Russian].23. Tomarov I. Avtorskoe pravo na dokumenty, sozdannye juristom. Legal Shift. 26.03.2017. URL: http://www.legalshift.com.ua/?p=856 [in Russian].24. Digital and Digitized Assets: Federal and State Jurisdictional Issues. American Bar Association, Derivatives and Futures Law Committee, Innovative Digital Products and Processes Subcommittee, Jurisdiction Working Group. December 2020. 403 p. URL: https://www.americanbar.org/content/dam/aba/administrative/business_law/buslaw/committees/CL620000pub/digital_assets.pdf25. Kardonov A. Sfery primenenija smart-kontraktov i riski pri rabote s nimi. Biznes obrazovanie v jekonomike znanij. 2018. No. 1. P. 44-47 [in Russian].26. Jagubova U.R. Problemy primenenija norm dogovornogo prava k smart-kontraktam, osushhestvljaemym v informacionnoj platforme blokchejn (blockchain). Vestnik sovremennyh issledovanij. 2018. No. 4-1. P. 394-396 [in Russian].27. Zimneva S.V., Luk'janenko M.F. Dobrosovestnost' i razumnost' povedenija kak osnovanie osvobozhdenija ot grazhdansko-pravovoj otvetstvennosti. Gosudarstvo i pravo. 2017. No. 8. P. 42-49 [in Russian].28. Mik E. Smart Contracts: terminology, technical limitations and real world complexity. Law, Innovation & Technology. 2017. No. 9. P. 8-12.29. Nekit K.H. Perevahy ta nedoliky smart-kontraktiv yak pidstav vynyknennia prava vlasnosti. Visnyk Natsionalnoho tekhnichnoho universytetu Ukrainy “Kyivskyi politekhnichnyi instytut”. Politolohiia. Sotsiolohiia. Pravo. 2020. No. 3 (47). P. 101-105. https://doi.org/10.20535/2308-5053.2020.3(47).229494